Efficacy of an Experimental Gonococcal Lipooligosaccharide Mimitope Vaccine Requires Terminal Complement. (31st December 2021) - Lewis, Lisa A; Gulati, Sunita; Zelek, Wioleta M; Morgan, B Paul; Song, Wen-Chao; Zheng, Bo; Nowak, Nancy; DeOliveira, Rosane B; Sanchez, Bryan; DeSouza Silva, Leandro; Schuurman, Janine; Beurskens, Frank; et al.
Abstract: A safe and effective vaccine against multidrug-resistant gonorrhea is urgently needed. An experimental peptide vaccine called TMCP2 that mimics an oligosaccharide epitope in gonococcal lipooligosaccharide, when adjuvanted with glucopyranosyl lipid adjuvant–stable emulsion, elicits bactericidal immunoglobulin G and hastens clearance of gonococci in the mouse vaginal colonization model. In this study, we show that efficacy of TMCP2 requires an intact terminal complement pathway, evidenced by loss of activity in C9 −/− mice or when C7 function was blocked. In conclusion, TMCP2 vaccine efficacy in the mouse vagina requires membrane attack complex. Serum bactericidal activity may serve as a correlate of protection for TMCP2. Abstract : An experimental gonococcal peptide vaccine that mimics a gonococcal glycan epitope on lipooligosaccharide requires activation of the terminal complement pathway for its efficacy in the mouse vaginal colonization model of gonorrhea.